2005
DOI: 10.1111/j.1365-2672.2004.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pH of growth on the survival of Lactobacillus delbrueckii subsp. bulgaricus to stress conditions during spray-drying

Abstract: Aims: The aim of this study was to optimize survival of Lactobacillus delbrueckii subsp. bulgaricus during spraydrying and subsequent storage through optimizing the pH of growth conditions. Methods and Results: Cell concentrates previously grown without or with pH controlled were spray-dried and stored at 20°C and heat treated at 57°C. Cells grown under noncontrolled pH were more resistant to both drying and heating than cells grown under controlled pH but no significant differences were observed during storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 37 publications
3
54
0
1
Order By: Relevance
“…Several reports have suggested that improved stress tolerance can be achieved if cells are mildly stressed during growth [29,36], and correlations between membrane lipid compositions of different Lactobacillus spp. and their freeze tolerance (cryotolerance) have been demonstrated [1,35].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have suggested that improved stress tolerance can be achieved if cells are mildly stressed during growth [29,36], and correlations between membrane lipid compositions of different Lactobacillus spp. and their freeze tolerance (cryotolerance) have been demonstrated [1,35].…”
Section: Introductionmentioning
confidence: 99%
“…The pH and temperature of the control culture (MRS broth) were 6.5 and 37 o C, respectively, according to manufacturer's recommendation and as described previously (Boot et al, 1993;Silva et al, 2005;Smit et al, 2001). …”
Section: Stress Conditionsmentioning
confidence: 99%
“…Previously, we found that up to 16-to 18-fold better survival of L. paracasei NFBC 338 spray-dried in RSM (20%, wt/vol) occurred at outlet temperature 95 to 105°C as a result of salt or heat adaptation (6), while another study demonstrated that growth at an uncontrolled pH increased the survival of Lactobacillus delbrueckii subsp. bulgaricus after spray-drying up to 10-fold, which was linked to overexpression of GroEL (20). A comparison of these data indicated that although GroESL plays a major role in the survival of L. paracasei NFBC 338 during exposure to stress, it is part of a wider arsenal of mechanisms (5).…”
mentioning
confidence: 99%